THE USE OF YOUTUBE CHANNEL â€œLINGUA MARINAâ€ IN ENHANCING STUDENTS' PERFORMANCE OF SPEAKING - Haris Hamdani; Ferawaty Puspitorini; Rully Khoeru Solihin (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
Students should be able to master four skills in English. They may find it challenging to learn certain skills, particularly speaking. They are hesitant to improve their speaking skills since they do not receive assistance from the environment. The surroundings are not in English. The study aimed at finding out studentsâ€™ perception of use of YouTube the Channel â€œlingua marinaâ€ in enhancing studentsâ€™ performance of speaking. The subjects of this research were 10 psychology students of Universitas Bhayangkara Jakarta Raya in the fourth semester. The researchers applied the descriptive qualitative method to this study. The data were gathered through questionnaires and interviews. The data were interpreted in the words to show the results of questionnaire and interview. Based on the result of the study, most students agreed that YouTube videos help them increase new vocabulary, when they learn using YouTube videos they can improve their pronunciation, they can speak English fluently using YouTube videos, they shared â€œneutralâ€ for a better understanding of the material when they watch YouTube videos, they also shared â€œneutralâ€ that YouTube videos cannot make them bored when learning English, they enjoy practicing speaking English using YouTube videos, they agree that YouTube videos can be a motivational tool in learning to speak English, YouTube videos can help them use good pronunciation, they shared â€œneutralâ€ that they can organize the ideas using YouTube videos, and they can better understand in guessing unfamiliar words using YouTube videos. Ten students were interviewed about the use of YouTube Videos to improve their speaking skill, and most of them could learn English easily using YouTube videos. They could increase their motivation. They could imitate foreigners speaking English repeatedly and fluently. Finally, they felt easy to memorize new vocabulary vocabularies. To sum up, students can be helped in enhancing their speaking skill by utilizing YouTube videos.